Photomechanochemistry: harnessing mechanical forces to enhance photochemical reactions - Mele, Francesco; Constantin, Ana Maria; Porcheddu, Andrea; Maggi, Raimondo; Maestri, Giovanni; Ca’, Nicola Della; Capaldo, Luca (Beilstein Journal of Organic Chemistry, 2025)
Photomechanochemistry, i.e., the merger of light energy and mechanical forces, is emerging as a new trend in organic synthesis, enabling unique reactivities of fleeting excited states under solvent-minimized conditions. Despite its transformative potential, the field faces significant technological challenges that must be addressed to unlock its full capabilities. In this Perspective, we analyze selected examples to showcase the available technologies to combine light and mechanical forces, including manual grinding, vortex and shaker mixing, rod milling, and ball milling. By examining the advantages and limitations of each approach, we aim to provide an overview of the current state of synthetic photomechanochemistry to identify opportunities for future advancements in this rapidly evolving area of research.
Keywords: light-mediated synthesis; mechanochemistry; photomechanochemistry